Explorando em campo minado: a sinuosa trajetória intelectual de Manuel Bomfim em busca da identidade nacional - Uemori, Celso Noboru (2006)
Manoel Bomfim (1868-1932) was for a long time a relegated author, as several interpreters have affirmed. Bomfim went out of the ostracism thanks to initiatives of intellectual entailed to the Estado Novo, (1937-1945), who saw in his thoughts inspiration for the search of the brasilidade roots and for the exhortation of nationalism. Later, intellectuals of left saw the originality and the courage of a First Republic thinker who opposed radically to the followers of the scientific racism, who analyzed the country's history revealing the Iberian colonialism role in the formation of the conservative mentality of the dominant class and, also, the economic and political foundations of the delay of the country, getting away, this way, of the vogue of the racial and climatic determinism. Nowadays, his work is object of the interest of academic researchers and press professionals. Bomfim's ideas are still important because his battle for the education and his effort to comprehend the reasons of Brazil's failure as a nation. This thesis analyses the following subjects: 1) How Bomfim retook ideas and elaborated concepts, in Europe, with conservative purposes, and re-worked them to criticize the dominant and, as well, to think the voluntary servitude of the dominated; 2) The importance of Darwin's ideas for the development of main concepts of Bomfim's thought, like the solidarity, the criticism to the racism and to occidental ethnocentrism and his anti belligerence position; 3) The ambiguity of Bomfim's speech on the nationality formation, stressing that the nation just as it is described in the book A América Latina (1905) is not the same nation that appears on the book O Brasil na América (1929); 4) the dichotomist relationship between State parasite and its "hostess", the nation.. As a conclusion, I highlight the originality of a thought that built itself inside the complex tangle between the author's personal options and the influence of the political and cultural context of his time